An Analysis of American Indian Homicide: A Test of Social Disorganization and Economic Deprivation at the Reservation County Level - Bachman, Ronet (Journal of research in crime and delinquency, 1991)
Although homicide rates among the American Indian population are documented to be double that of the White population, criminologists have devoted little attention to examining the etiology of American Indian homicide. This article presents a multivariate analysis of American Indian homicide at the reservation county level. The model tests indicators of social disorganization and economic deprivation while controlling for other demographic variables. Results indicate that both social disorganization and economic deprivation contribute to high levels of lethal violence in reservation communities